Perioperative pain management for hip fracture patients. Issue 2 (April 2016) - Freeman, Nicholas; Clarke, Jamie
Abstract: A hip fracture is the most common reason for admission to an orthopaedic ward, yet the management of acute pain in this group of patients is often difficult. Good multi-modal analgesia is important to reduce the incidence of delirium, which is frequently a problem. Other challenges involve age related differences in pharmacokinetics and pharmacodynamics, which can make drug selection more complicated. This article discusses delirium (its causes and how to treat it); the assessment of pain (including in the cognitively impaired); reviews the drugs commonly available to clinicians progressing through the WHO pain ladder, including opioid-sparing techniques (i.e. local anaesthetic nerve blocks). The rationale for recommending intravenous paracetamol, oral oxycodone (instead of morphine) and fascia iliaca blocks are also explored. Finally, suggested pain pathways are described.